The Influence of Corporate Governance Mechanisms and Investment Opportunity Set on Earnings Management - Malinda Kharista (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The aim of this study was to analyze the influence of corporate governance mechanisms and investment opportunity set on earnings management practices in Indonesia. This study used a sample of 20 manufacturing companies listed in the Indonesia Stock Exchange (IDX) in 2010-2014 and the sample selection is based on judgment sampling. Results from this study showed corporate governance mechanisms has no affect on earnings management practices and investment opportunity set negatively affect earnings management practices. This is because the implementation of corporate governance is still relatively new in Indonesia so the goal has not been effectively felt. In addition, the corporate governance implementation has started being applied in the business world, but implementation still not fulfilled either. Earnings management practices cannot be fully carried out by only having a great number of investment opportunity set. Companies that have the auditor from the Big 5 will have lower possibility of discretionary accruals actions undertaken by management. Key Words: Corporate Governance Mechanisms, Investment Opportunity Set, Earnings Management.